ChemInform Abstract: Conversion of Phenols into Selenophenols: Seleno Newman—Kwart Rearrangement. Issue 16 (22nd April 2014) - Soerensen, Anne; Rasmussen, Brian; Agarwal, Shubham; Schau‐Magnussen, Magnus; Soelling, Theis I.; Pittelkow, Michael
Abstract This rearrangement works best with electron‐withdrawing substituents in ortho‐ and/or para‐position due to a lower energy barrier of activation.